2017
DOI: 10.1590/0034-7167-2016-0189
|View full text |Cite
|
Sign up to set email alerts
|

Hand hygiene as a caring practice: a reflection on professional responsibility

Abstract: Hand hygiene represents a fundamental nursing care practice and is traditionally considered the most important and effective measure in the prevention and control of healthcare-related infections. However, studies indicate that adherence to the procedure is unsatisfactory throughout the world, and show low adherence rates. In a context in which patient safety stands out as a priority, this text submits refl ections about professional responsibility when not adhering to hand hygiene practices, and ethical aspec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
12

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 8 publications
0
13
0
12
Order By: Relevance
“…Furthermore, professionalism emerged as another key facilitator to hand hygiene compliance, which has been previously reported 48 . Finally, hand hygiene policy was a motivator for the participants to engage in more vigilant hand hygiene 4 .…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Furthermore, professionalism emerged as another key facilitator to hand hygiene compliance, which has been previously reported 48 . Finally, hand hygiene policy was a motivator for the participants to engage in more vigilant hand hygiene 4 .…”
Section: Discussionmentioning
confidence: 61%
“…Patients were also identified as key supportive people, complementing the findings of a study emphasizing their potentially convincing role in enhancing hand hygiene compliance among HCWs 44 . For the important people not supportive of hand hygiene, the strongest theme to emerge was reports of non-compliance and active discouragement of hand hygiene from some senior doctors, reported also in previous studies 45,46 , but not others 47,48 where senior physicians supported hand hygiene initiatives. Addressing doctors' beliefs is particularly important given the leadership roles they play in healthcare settings 22 .…”
Section: Discussionmentioning
confidence: 79%
“…A lavagem das mãos antes e depois dos procedimentos foi a ação elencada como prioritária no controle de infecção. Ao considerar que as mãos dos profissionais são as principais responsáveis pela disseminação de microrganismos, higienizá-las é medida simples e eficaz para prevenir infecções associadas à assistência, com boa relação custo-benefício 13,14 . O profissional, ao aderir a essas medidas, contribui para o desenvolvimento da qualidade da assistência aos usuários, com benefícios na redução da morbimortalidade 12 .…”
Section: Discussionunclassified
“…Recent research has demonstrated the importance of promoting adequate HH technique compliance among health professionals in order to reduce the high rates of infections caused by multidrug resistant microorganisms (4)(5)(6)(7)(8)(9) . However, low compliance with these practices remains a challenge for practitioners and health institutions, especially in developing countries, which may present an HCAI rate up to 20 times higher than in developed countries (10) .…”
Section: Introductionmentioning
confidence: 99%